2010
DOI: 10.1177/1049732309358329
|View full text |Cite
|
Sign up to set email alerts
|

Metasynthesis of the Hope Experience of Family Caregivers of Persons With Chronic Illness

Abstract: The purpose of this metasynthesis was to describe the hope experience of family caregivers of persons with chronic illness. Fourteen studies were included in the metasynthesis. All studies described the importance of hope to the family caregivers of relatives with chronic illness regardless of age, relationship, or setting. Several derived themes arose from the metasynthesis, including (a) transitional refocusing from a difficult present to a positive future, (b) dynamic possibilities within uncertainty, (c) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
141
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 35 publications
(73 reference statements)
5
141
0
4
Order By: Relevance
“…The Critical Appraisal Skills Programme [CASP] (2013) was utilised, comprising of 10 questions to assess the credibility, rigour and relevance of the research. However, as well as referring to qualitative comments from the CASP (2013), comments were quantified to obtain an overall quality score (Duggleby et al, 2010). A strong score of '3' denoted extensive justification and meeting of criteria, a moderate score of '2' denoted addressing, but not elaborating on the issue, and a weak score of '1' denoted a substantial lack in meeting 7 criteria or presenting justification.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…The Critical Appraisal Skills Programme [CASP] (2013) was utilised, comprising of 10 questions to assess the credibility, rigour and relevance of the research. However, as well as referring to qualitative comments from the CASP (2013), comments were quantified to obtain an overall quality score (Duggleby et al, 2010). A strong score of '3' denoted extensive justification and meeting of criteria, a moderate score of '2' denoted addressing, but not elaborating on the issue, and a weak score of '1' denoted a substantial lack in meeting 7 criteria or presenting justification.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…10 Hope is a multidimensional and dynamic construct which has been defined as the possibility of a better future from an uncertain present. 11 Literature revealed that hope is an important factor in the recovery of cancer patients 12 Cancer patients appears to be more influenced by the level of hope than other diseases. 13 For example as hopelessness is a risk factor for suicide 14 thus, identifying factors that affects the hope of cancer patients specially newly diagnosed patents is of great importance.…”
Section: Copyright © 2015 By Tabriz University Of Medical Sciencesmentioning
confidence: 99%
“…The reviewers used a three-point 23 system to rate each paper on how it explained each of the eight areas (weak = 1, moderate = 2, strong = 3) [22].…”
mentioning
confidence: 99%
“…Scores were then summed for each paper, giving a possible score of [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. This quality review was 26 conducted to aid readers' critical consideration of the credibility of the included papers' findings, and as such 27 papers were not excluded on the basis of their scores, Furthermore, as ratings on CASP criteria tend to reflect the 28 quality of reporting rather than that of the research undertaken, and do not necessarily indicate the robustness, 7 *** Table 1 about here ***…”
mentioning
confidence: 99%